Vortex dynamics in a 2-dimensional starting jet - Chan, Kenneth Jun Pin. (2013)
Experimental studies of the evolution of a two-dimensional vortex pair induced by a starting jet is carried out. The dynamics of the flow is computed in detail and its recalibrated data is studied in detail. Based on the experimental data, we can analyze the pinch-off of the vortex flow. The results show the pinch off process starts at t= 9 and subsequent pinch offs coming at a faster rate as its breaks off from its trailing jet. The total and local circulation is also computed and compared to its theoretical results to ascertain the accuracy of assumptions made by other papers. Normalized energy is also studied to see how the energy changes during different formation times and what the results represents. The experimental results analyzed were subjected to certain parameters, such as the Reynolds number, velocity profile and geometry, velocity programme and its vortex generation method.